Environmental Impact Assessment Of Abrasive Materials In Industrial Blasting Process - Amin, Iskandar Zulkarnain Mohd (2024)
The environmental impact study of abrasive materials in the blasting industry is a pivotal research endeavour. Abrasive blasting, widely used in surface preparation and painting industries, involves projecting high-pressure abrasive material onto surfaces. This research aims to characterize various abrasive materials and assess their environmental impact. Various proposed abrasive materials, including diamond, garnet, jadecut, ceramic, and two types of glass (Duragrit glass and Glass blast), undergo a meticulous examination of their compound composition and crystallinity, utilizing X-ray Fluorescence (XRF) and X-ray diffraction (XRD) analyses. Both Duragrit glass and Glass blast emerge as promising candidates, displaying an amorphous structure and meeting the Department of Occupational Safety and Health (DOSH) requirements for open blasting. Mechanical properties of these materials are thoroughly characterized, including particle size distribution (ISO11127-2), apparent density (ISO11127-3), hardness (ISO11127-4), moisture content (ISO11127-5), and water-soluble chlorides (ISO11127-7). For instance, apparent density measures 2.17 × 103 kg/m3 for Duragrit glass and 2.5 × 103 kg/m3 for Glass blast, with moisture content at 0.01%. Water-soluble chlorides are Nil for Duragrit glass and 0.0001% for Glass blast. These findings are foundational for effective abrasive blast-cleaning, ensuring safety compliance, and preserving desired surface features. The efficacy of Duragrit glass and Glass blast in surface preparation adheres to industry standards, meeting Petronas Technical Specifications (PTS) and Shell Technical Specifications (STS) requirements.